Embedding Metal–Organic Frameworks for the Design of Flexible Hybrid Supercapacitors by Electrospinning: Synthesis of Highly Graphitized Carbon Nanofibers Containing Metal Oxide Nanoparticles. Issue 9 (8th July 2022) - Li, Yanjiang; Zhu, Guang; Xu, Xingtao; Chen, Lei; Lu, Ting; Hill, Jonathan P.; Pan, Likun; Yamauchi, Yusuke
Abstract : Electrospun carbonaceous fibers have emerged as promising electrode materials for application in energy storage devices. However, their relatively poor electrical conductivity (due to their amorphous carbon structures) and low capacitive performance lead to poor prospects for their further application. Herein, a universal synthesis of highly graphitized carbon nanofibers, containing various metal oxide nanoparticles (e.g., Fe2 O3, NiO), by the pyrolysis of metal–organic framework (MOF)‐embedded electrospun nanofibers, is reported. The resulting carbon nanofibers exhibit large mesopore volumes, contain large quantities of Faradic metal oxide nanoparticles, and are highly graphitized. The fibers also have excellent mechanical flexibility, provide fast ion transfer characteristics, and a large pseudocapacitance combined with excellent electrical conductivity, leading to large specific capacitances. Consequently, asymmetric flexible hybrid supercapacitors assembled from Fe2 O3 ‐embedded highly graphitized carbon nanofibers (FOCNF) and NiO‐embedded highly graphitized carbon nanofibers (NOCNF) exhibit a high energy density of 43.1 Wh kg −1 at a power density of 412.5 W kg −1 and possess excellent flexibility (capacitance retention of 94.4% at 180° bending and 96.2% at 30° twisting) with superior cycling stability. This strategy provides a new MOF‐based approach for the design and synthesis of multifunctional flexible carbonaceous materials and might lead to their further application in flexible energy storage devices. Abstract : Highly graphitized carbon nanofibers with metal oxide nanoparticles are synthesized based on the metal–organic framework‐based electrospinning approach. The representative examples with Fe2 O3 and NiO nanoparticles demonstrate high electrochemical performances, showing potential application as active materials for flexible hybrid supercapacitors.